Simultaneous Chronic Lymphocytic Leukemia and Hairy Cell Leukemia: a Sporadic Event? A Semantic Point of View. - luiza akria; celia suriu; ytzkak cohen; judith chezar; andrei braester (Mediterranean Journal of Hematology and Infectious Diseases)
The coexistence of CLL and HCL has already been reported in the literature, but as an exceedingly rare event, because the presentation (clinical and laboratory) was generally a CLL-like one and HCL was discovered "by the way". To prove that the concomitance between these two diseases is not as rare as previously believed, we have to think "semantically": the question is not how many CLL cases are concomitant with HCL, but how many HCL cases are concomitant with CLL. Chronic Lymphocytic Leukemia (CLL) originates from antigen-stimulated mature B lymphocytes and is the most common type of leukemia in older adults, it accounts for25% of all leukemia cases. Hairy Cell Leukemia (HCL) is also a chronic lymphoproliferative disorder originating from mature B lymphocytes. HCL accounts for 2-3% of all leukemia cases. The male to female ratio is approximately 4:1. The etiology is not known. CLL and HCL have distinct clinical, morphological and immunophenotyping features. The occurrence of second neoplasm in HCL patients is well-known, especially non-Hodgkin's lymphomas. In the last 10 years we diagnosed in our hemato-oncologic clinic 22 cases of HCL, 4 of them (18 % of all cases of HCL diagnosed during this period) with concomitant both diseases. We did not performed immunoglobulin gene rearrangement analysis, so we can not know if the origin is from different B cell clones or not; we can only afirm that on the membrane of both CLL and HCL cells was present the same light chain type. We mention that all cases of lymphoprolipherative disorders (LPD) are systematically screened for the presence of an additional monoclonal B-cell population. Conclusion: we want to challenge the concept that concomitant CLL and HCL is a rare event. It's only a "trompe l'oeil", due to the rarity of HCL.